The influence of materialistic and ethical values on the purchase intention of counterfeit luxury goods: The case of Malaysian undergraduate - Ong, Derek Lai Teik *; Ahmad Khairul Ariffin bin Kamaruddin, *; Bulathsinghalage, Channaka Nadira *; Seneviratne, Luke Aaron (IBIMA Publishing, 2013)
This study aims to measure Malaysian undergraduate students’ ethical and materialistic values, and their relationships with the purchase intention of non-deceptive luxury counterfeit goods. 200 questionnaires were distribute physically and via online. Items were adapted from the Muncy-Vitell, Spears-Singh, and Belks scales to measure ethics, purchase intention, and materialism, respectively. Findings showed that a significant relationship between ethics and materialism exists as respondents who are reported to be ethical were also materialistic. These variables were also found to be significantly related to purchase intention. Ethical and materialistic consumers were less likely to report prior purchase of counterfeits. Also, the findings in this paper suggest that level of affluence does not have much significant impact on the relationship between these two variables with identifying their purchasing intentions. The results show that increasing awareness and knowledge of undergraduate students on the impact of counterfeiting can lead to more ethical purchasing behaviors. However, the fact that limitations were that the majority of respondents were Chinese and were only from limited areas makes generalizing findings to all undergraduate students across Malaysia inappropriate. This study further elaborates the demand of counterfeit goods through the effects of ethics and materialism. Improved efforts against counterfeiting can now be made by altering consumers’ ethical values and exploiting their materialistic tendencies.